Interaction of Mouse and Sheep Polyclonal Antibodies with the Main Forms of Human and Rat Renalase - Fedchenko, V.I.; Kaloshin, A.A.; Kaloshina, S.A.; Medvedev, A.E. (Biomedical Chemistry: Research and Methods, 2024)
The interaction of sheep and mouse polyclonal antirenalase antibodies obtained by immunization with full-length human (RNLS1-human) and rat (RNLS2-rat) renalases, respectively, has been studied. The target recombinant proteins, RNLS1-human and RNLS2-rat, were expressed in E. coli cells and isolated by Ni-agarose chromatography. Sheep polyclonal antibodies against RNLS1-human interacted more effectively with both RNLS1-human than with RNLS2-rat. Mouse polyclonal antibodies against RNLS2-rat effectively interacted mainly with RNLS2-rat, but not with RNLS1-human. The data obtained indicate the preferential selectivity of the antibody interaction with the proteins against which they were obtained. This should be taken into consideration in the case of selection of commercially available antibody preparations for quantitative immunodetection of target proteins in biological objects.